2017
DOI: 10.1111/bcpt.12829
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine Reduces Digitalis‐induced Ventricular Arrhythmias

Abstract: The I channel inhibitor ivabradine is recommended for treatment of heart failure but also affects potassium currents and thereby prolongs ventricular repolarization. The aim of this study was to examine the electrophysiological effects of ivabradine on digitalis-induced ventricular arrhythmias. Thirteen rabbit hearts were isolated and Langendorff-perfused. After obtaining baseline data, the digitalis glycoside ouabain was infused (0.2 μM). Monophasic action potentials and ECG showed a significant abbreviation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The bradycardic features of ivabradine raise the question of whether it could be effective in ventricular arrhythmias. Recently, ivabradine was found to decrease digitalis-induced ventricular arrhythmias and short QT-induced arrhythmic features in Langendorff-perfused rabbit heart preparations (Frommeyer et al, 2017a;Frommeyer et al, 2017b). Along with this rationale, we asked in the present work whether ivabradine could prevent the ventricular arrhythmias found in cellular and animal models of CPVT2.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The bradycardic features of ivabradine raise the question of whether it could be effective in ventricular arrhythmias. Recently, ivabradine was found to decrease digitalis-induced ventricular arrhythmias and short QT-induced arrhythmic features in Langendorff-perfused rabbit heart preparations (Frommeyer et al, 2017a;Frommeyer et al, 2017b). Along with this rationale, we asked in the present work whether ivabradine could prevent the ventricular arrhythmias found in cellular and animal models of CPVT2.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, it was shown that ivabradine blocks the recombinant hERG current over a range of concentrations overlapping with those required to block HCN4 (Melgari et al, 2015). Because of its concurrent inhibitory action on If and IKr currents, ivabradine was suggested to be a potential antiarrhythmic drug thanks to an increase in both the effective refractory period and the post-repolarization refractoriness (Frommeyer et al, 2017a;Frommeyer et al, 2017b). The bradycardic features of ivabradine raise the question of whether it could be effective in ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ivabradine is known to prolong ventricular repolarization and alter electrical restitution properties of the myocardium in both in vitro cellular models and perfused guinea pig hearts via inhibition of hERG/I Kr channels 14,15 and has been shown to mitigate digitalis‐induced ventricular arrhythmias 16 . Similar beneficial effects on ventricular arrhythmogenesis have been noted in humans with heart failure (LVEF < 35%) where ivabradine markedly decreased dobutamine‐induced ectopy 17 .…”
Section: Discussionmentioning
confidence: 86%
“…Ivabradine reduced inducible VA in a Langendorff-perfused rabbit heart in the model of short-QT syndrome induced by a potassium channel opener, pinacidil [ 66 ] as well as digitalis-induced VA in the same rabbit model [ 67 ], while it was proarrhythmic in a model of long QT syndrome [ 68 ].…”
Section: Ivabradine and Ventricular Arrhythmiasmentioning
confidence: 99%